Analisis Efektivitas Sistem Produksi dengan Metode Troubleshooting pada PT Chandra Nugerah Cipta - Muhamad Sodikin; Ade hendrik; Agung Budi Wibowo; Ferdyansyah; Dwi Irwati (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2025)
PT Chandra Nugerah Cipta produces components and frames for cars and motorcycles. To speed up its production process, CNC Group has moved into manufacturing and engineering. They make components and spare parts for two-wheeled and four-wheeled vehicles using welding and pressing processes. PT Chandra Nugrah Cemerlang employs Yamaha, Astra Honda Motor, and Kawasaki. One of the production processes to be studied is the PT CNC 3 engraving machine line, which consists of twenty engraving machines and three manual engraving machines of the Otc Daihen type. Manual engraving machines are used to improve poor robotic engraving results or repairs. To face global competition, PT CNC Group is committed to improving productivity, culture, and human resources. Keywords: efficiency,Effectiveness,Troubleshooting